Clinical efficacy and safety of endoscopic retrograde appendicitis treatment for acute appendicitis: A systematic review and meta-analysis - Xu, Zhigang; Jin, Liang; Wu, Wenjiang (Clinics and research in hepatology and gastroenterology, 2023)
•Endoscopic retrograde appendicitis treatment is a well-established treatment for patients with AUA, showed promising results.•Endoscopic retrograde appendicitis treatment is a feasible and safe treatment option for the treatment of acute appendicitis.•Endoscopic retrograde appendicitis treatment preserves appendix intactly, which is thought to play a role in immune function. To assess the efficacy and safety of endoscopic retrograde appendicitis treatment (ERAT) for acute appendicitis (AA) by conducting a meta-analysis of clinical randomized trials (RCTs). Eight electronic databases were searched. Study quality was assessed using the Cochrane risk of bias tool. RevMan5.3 and STATA14 software were used to for statistical analysis. Twenty-six RCTs with 2236 subjects were analyzed. First, operative time, length of hospital stay and duration of bed rest were shorter in the ERAT groups than in the control groups, with the pooled MD and 95 % CI being -13.22(-20.09, -6.35)(p = 0.0002), -2.13 (-2.47, -1.80)(p < 0.00001) and -3.15 (-3.76, -2.53)(p < 0.00001), respectively. Second, patients in the ERAT groups had a lower incidence of complications than the control groups, with a pooled RR and 95 % CI of 0.25(0.18, 0.35)(p < 0.00001). Third, patients who received ERAT returned to normal temperature faster than the control groups, the pooled MD and 95 % CI was -3.39(-4.36, -2.42)(p<0.00001). Finally, the result showed that the recurrence rate in the ERAT groups was approximately twice that of control groups, with the pooled RR and 95 % CI being 2.10(1.02, 4.32)(p < 0.00001). ERAT results in fewer complications and shorter recovery time. And compared to appendectomy, ERAT reduces operative time and intraoperative bleeding. However, the recurrence of acute appendicitis after ERAT remains a concern. And more multicenter and large-scale RCTs are needed to confirm the benefits of ERAT. We have registered on the PROSPERO [https://www.crd.york.ac.uk/PROSPERO/], and the registration number is CRD42023420171.